Eksistensi Penerapan Konsep Restorative Justice dalam Upaya Penyelesaian Sengketa Perdata di Indonesia - Khalimatus Shafira, Shelly; Amelia Putri, Sifa; Ainurohwati, Yessi; Zaki Mubarok, Ahmad (UNIVERSITAS SERAMBI MEKKAH, 2024)
Dispute resolution is an essential part of law enforcement, encompassing both litigation and non-litigation methods such as restorative justice. Restorative justice emphasizes dialogue and reconciliation between the involved parties, prioritizing restoration over punishment. This article discusses the restorative justice approach in resolving civil disputes as an alternative to litigation. Although this method was initially applied in criminal law, its use in civil disputes has increasingly developed. This study examines the concept and effectiveness of restorative justice in resolving civil disputes in Indonesia, using a normative juridical approach and descriptive analysis to evaluate its effectiveness within the Indonesian legal context. The results indicate that while restorative justice holds potential in offering a more humane and sustainable solution for civil dispute resolution, its implementation still faces challenges, including the lack of public understanding of the concept and the gap between formal law and customary law.